Pengaruh Sosialisasi Perpajakan, Pemahaman Peraturan Perpajakan dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak UMKM Setelah Penerapan PP No. 23 Tahun 2018 - Asmedi, Syamsul; Komalasari, Rosdiana (UNPERBA, 2024)
This study aims to analyze the effect of tax socialization, understanding of tax regulations, and tax rates on tax compliance of MSME taxpayers. The research method used is quantitative. The data used uses primary data taken from survey methods with data collection questionnaires through links with MSME taxpayer respondents. Questionnaires that can be processed amount to 80 questionnaires and samples using purposive sampling method. The statistical method used to test the hypothesis is multiple regression analysis. The results of the study simultaneously show that the variables of tax socialization, understanding of tax regulations, and tax rates have a significant effect on the tax compliance of MSME taxpayers. Partially it affects that the tax socialization variable does not have a significant effect on the tax compliance of MSME taxpayers. The variable understanding of tax regulations has no significant effect on the tax compliance of MSME taxpayers. And the results of tax rates have a significant effect on MSME taxpayer tax compliance.